Evolutionary lineage of naked harmful dinoflagellates, karlodinium/karenia/takayama/gyrodinium complex (Dinophyceae) - Chow, Luan Jia (Universiti Malaysia Sarawak (UNIMAS), 2011)
The genera of Karlodiunim, Karenia, Takayama, Gyrodinum are naked (athecated) dinoflagellates that have the potential to cause harmful algal blooms through the production of toxins or by their accumulated biomass, which can affect co-occurring organisms and alter food-web dynamics. In this study, we examine the phylogenetic lineage of Karlodiunim, Karenia, Takayama, Gyrodinium complex by mapping the morphological characters onto the phylogenetic tree. Using LSU rRNA gene sequences inferences, Karlodinium and Takayama phylogenies each revealed two monophyletic groups respectively whereas Karenia revealed three monophyletic groups and Gyrodinium revealed only one monophyletic group. Character mapping onto the LSU phylogeny revealed that different genera possess different morphological characters as the major morphological traits for species delineation. It appears that only certain classic morphological features (length and shaped of apical groove, cingulum displacement, sulcus structure, present of ventral pore) are of phylogenetic significance. The other characters such as the shape of epicone and hypocone somehow show high levels of variety and possess no taxonomic diagnostic value in the genera. These characters did not strongly support any grouping of taxa and appeared to have evolved in a random fashion.